Phylogeny and systematics of African Melastomateae (Melastomataceae) - (:unkn) unknown (My University, 2017)
Melastomateae are the most species-rich (185 spp./13 gen.) and morphologically diverse tribe within the African Melastomataceae. In this study we present the first in-depth phylogenetic analysis of African Melastomateae using sequences generated from one nuclear (nrITS) and two plastid spacers (accD-psaI, psbK-psbL) sampling 183 accessions representing 75 African, 10 Madagascan and 7 Asian species and a broad outgroup sampling. We infer phylogenetic relationships using maximum likelihood, maximum parsimony and Bayesian approaches and propose a revised generic classification of African Melastomateae based on our molecular trees in combination with a careful reassessment of morphological variation. Our phylogenetic analyses support the monophyly of Old World Melastomateae except Dinophora which clearly falls outside Melastomateae. Asian and Madagascan endemic genera of Melastomateae are nested among the African genera. Of the African genera only two monophyletic groups, Dichaetanthera and Tristemma, are recovered in addition to the monospecific Pseudosbeckia lineage, while Antherotoma, Dissotis and Heterotis as currently circumscribed are polyphyletic. However, the subgenera and sections of these genera are mostly recovered as morphologically distinct and molecularly well-supported clades. Isomorphism versus dimorphism of the stamens is found to be an unreliable character when delimiting genera in Melastomateae. We propose the reinstatement of Argyrella and Dupineta, a new status at generic rank for Dissotis subg. Dissotidendron, a broadened circumscription of Guyonia (to include the species previously placed in Heterotis sect. Cyclostemma), and description of a new, monospecific genus Anaheterotis for the Heterotis pobeguinii lineage. Heterotis is maintained at generic rank but with a narrower circumscription in comparison to earlier treatments. We accommodate the rare Osbeckia porteresii lineage from Mt. Nimba (Guinea) within an expanded Melastomastrum
Keywords: African Research